Dynamics of returns to vocational education in China: 2010-2017 - Jie Chen; Francesco Pastore (Global Labor Organization (GLO), 2022)
In this paper, we use the Chinese General Social Survey data (2010-2017) to analyse the returns to different education qualifications. We additionally compare the returns to vocational education with returns to academic education, at both the upper secondary level and the tertiary level. Compared to those who only complete compulsory education, upper secondary graduates earn about 20% more, vocational college graduates earn 50%, and academic university graduates earn 75% more. At tertiary level, academic education pays better than vocational education, although the difference shrinks over the years. At upper secondary level, the evidence is indeterminate, depending on different econometric techniques (i.e., OLS, IV, Lewbel method, or PSM). These findings add to the limited quantitative evidence on returns to vocational education. The dynamics emerged from the findings echo the discussion on labor market mismatch and overeducation in China, which has important policy implications.
Keywords: I26; I25; J24; J31; C36; 330; dynamic; vocational education; academic education; upper secondary; tertiary; China